2021
DOI: 10.1186/s12903-021-01558-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of cleaning efficacy and force of cylindric interdental brush versus an interdental rubber pick

Abstract: Background Interdental brushes (IDB) are according to the actual evidence the first choice for cleaning interdental areas (IDR). Their size should be chosen individually according to the IDR morphology. However, interdental rubber picks (IRP) are appreciated better by the patients and are hence becoming more and more popular but the evidence regarding their efficacy is still limited. The aim of this in vitro study was to measure the experimental cleaning efficacy (ECE) and force (ECF) during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Moreover, it was confirmed that there was a positive correlation between the diameter of the IDBs and cleaning efficacy. This evidence supported the previous article’s claim that the size and specifications of oral hygiene aids such as IDBs should be accurately selected [ 22 , 23 ]. Herein, the plateau obtained after the 5th washing cycle shows the same tendency in other studies [ 11 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, it was confirmed that there was a positive correlation between the diameter of the IDBs and cleaning efficacy. This evidence supported the previous article’s claim that the size and specifications of oral hygiene aids such as IDBs should be accurately selected [ 22 , 23 ]. Herein, the plateau obtained after the 5th washing cycle shows the same tendency in other studies [ 11 ].…”
Section: Discussionsupporting
confidence: 86%
“…This is thought to be because the toothbrush has to be longer than the actual diameter to penetrate deeper as the shape of the actual tooth is concave. The cleaning efficacy of an IDB is influenced by the design and diameter of the IDB, and the size of the interdental space [ 26 , 27 ]. Therefore, further studies are needed on the effect of these factors like varying diameters and shapes of IDBs on cleaning efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the model basis, the experimental device developed in previous publications [ 7 , 8 ] was modified in such a way, that a situation adapted to the oral cavity is possible under reproducible conditions. Therefore, the current in-vitro model simulates even more realistically a patient situation of oral hygiene at home, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…for patients with dry mouth. As explained in detail in our previous publications [ 7 , 8 ] we used 3D printed replicas of human teeth to create different intraoral morphologies by a computer software (Autodesk Fusion 360, Autodesk Direct Limited, Hampshire, United Kingdom) which were printed by a 3D printer (Form 2, Formlabs Sommerville, MA, USA) in a stereolithography way by using liquid photopolymer resin (White Resin V04 (RS-F2-GPWH-04), Formlabs, Sommerville, MA, USA).…”
Section: Methodsmentioning
confidence: 99%